2015
DOI: 10.1002/joc.4415
|View full text |Cite
|
Sign up to set email alerts
|

Response of the North Atlantic wave climate to atmospheric modes of variability

Abstract: This study investigates the relationship between the wind wave climate and the main climate modes of atmospheric variability in the North Atlantic Ocean. The modes considered are the North Atlantic Oscillation (NAO), the East Atlantic (EA) pattern, the East Atlantic Western Russian (EA/WR) pattern and the Scandinavian (SCAN) pattern. The wave dataset consists of buoys records, remote sensing altimetry observations and a numerical hindcast providing significant wave height (SWH), mean wave period (MWP) and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
4
34
0
1
Order By: Relevance
“…Within the Pertuis Breton, the NAO and EA/WR patterns respectively account for 25.2 and 20.6% of the winter (December to February) longshore sediment transport variability, while the contribution of EA pattern is minor (3.6%) and that of SCAN is not significant. Longshore sediment transport increases with positive NAO and negative EA/WR conditions (Poirier et al, 2017), both being associated with higher offshore and nearshore waves in the area (Martínez-Asensio et al, 2016).…”
Section: Wave Climatementioning
confidence: 99%
“…Within the Pertuis Breton, the NAO and EA/WR patterns respectively account for 25.2 and 20.6% of the winter (December to February) longshore sediment transport variability, while the contribution of EA pattern is minor (3.6%) and that of SCAN is not significant. Longshore sediment transport increases with positive NAO and negative EA/WR conditions (Poirier et al, 2017), both being associated with higher offshore and nearshore waves in the area (Martínez-Asensio et al, 2016).…”
Section: Wave Climatementioning
confidence: 99%
“…This would require further calibration, as the best-fit coefficients are site-specific. For instance, Martínez-Asensio et al (2016) demonstrated that while NW European Atlantic coasts experience above average wave energy conditions during high winter NAO+, the S European Atlantic coasts undergo the opposite (and vice versa for high winter NAO-). This in turn drives opposite shoreline response, as for instance during the winter 2009/2010.…”
Section: Weather Regime-driven Shoreline Modelmentioning
confidence: 99%
“…However, model skills strongly depend on the availability and quality of wave data. The characteristics of waves reaching the coast depend strongly on remote surface atmospheric circulation (e.g., Bacon and Carter 1993;Young 1999;Woolf et al 2002;Le Cozannet et al 2011;Charles et al 2012a;Martínez-Asensio et al 2016). Because waves are the primary driver of shoreline change along most coastlines, interannual shoreline variability is expected to be related to interannual large-scale atmospheric dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is widely accepted that large wave storms in the Atlantic Ocean are a direct consequence of the passage of extratropical cyclones, the details of this relationship at the regional scale need to be clarified, since it is not known whether the magnitude of the event is more closely related with the track or the depth of the forcing cyclones. Additionally, these cyclones usually propagate along preferred trails, so-called storm tracks, and the phases of enhanced or reduced storminess along European Atlantic coastlines are modulated by hemispheric-scale circulation patterns, known as teleconnections [14][15][16].…”
Section: Introductionmentioning
confidence: 99%